Evaluation of UV–HPLC and mass spectrometry methods for specific activity determination. (16th September 2014) - Elmore, Charles S.; Schenk, David J.; Arent, Robert; Kingston, Lee
<x xml:space="preserve">Abstract</x> The specific activity (SA) values determined using two different methods were compared for a set of tritium‐labeled and carbon‐14‐labeled compounds. The methods employed were as follows: (a) liquid chromatography/mass spectrometry (LC/MS) isotopic peak intensity distribution, and (b) determination of the tracer mass concentration using ultraviolet–high‐performance liquid chromatography analysis coupled with the radioactive solution concentration measured by liquid scintillation counting. In general, at lower SA, the accuracy and or precision of the LC/MS‐determined SA value decreased significantly. Because of this decrease in accuracy, a rough guideline of ~10% of the theoretical maximum SA is recommended as the lower cutoff for MS‐based SA measurements. If the tracer contains heteroatoms that possess significant percentages of heavy isotopes at natural abundance (e.g. Cl and Br), then the MS‐based SA cutoff recommendation is approximately 25–30% of the fully labeled compound in the tracer mixture. Additionally, IsoPat2 was found to be the preferred calculation method for LC/MS‐based SA determination because SA values via this program were more consistent with those obtained by ultraviolet concentration calibration with solution count.